'They Were Going to the Beach, Acting like Tourists, Drinking, Chasing Girls': A Mixed-Methods Study on Community Perceptions of Sexual Exploitation and Abuse by UN Peacekeepers in Haiti. Issue 1 (21st May 2020) - King, Carla; Lee, Sabine; Bartels, Susan A.
The United Nations Stabilization Mission in Haiti (MINUSTAH) has been marred by reports of sexual exploitation and abuse (SEA) perpetrated against local women/girls. However, there is very limited empirical evidence on the community's perceptions regarding these sexual interactions. Through a mixed-methods approach, this article examines community experiences and perceptions of SEA, with three prominent themes arising: peacekeepers as tourists, peacekeepers as sexual exploiters and abusers, and peacekeepers as ideal partners. Uruguayan (n = 107, 28.1 per cent) and Brazilian personnel (n = 83, 21.8 per cent) were most commonly named in SEA narratives. We explore how these perceptions of MINUSTAH peacekeepers undermine the purpose and legitimacy of UN peace support operations, and propose strategies to prevent and address peacekeeper-perpetrated SEA.